Penerapan Optimalisasi Marketplace untuk pemasaran produk pada UMKM keripik pare Alena Desa Damaran, Kecamatan Kota Kabupaten Kudus - Rhoedy Setiawan; Diana Laily Fithri; Andy Prasetyo Utomo; Fajar Nugraha (Muria Jurnal Layanan Masyarakat, 2022)
Damaran Village is one of the villages located in the sub-district of the City of Kudus Regency. In the village, there are MSMEs that process bitter gourd into snacks that are nutritious and very beneficial for health. So far, the production process and marketing of bitter gourd products are still carried out traditionally so that the quality and quantity of production are not optimal and the range of promotion is still limited around Kudus city, although there are some requests from outside the city the number is still small due to lack of promotion. The purpose of this community service is to help increase the income and welfare of the bitter melon chip craftsmen. The method of implementing the program is to make a vacuum fryer to fry bitter gourd into chips whose taste and nutrition are maintained. And create an internet platform to promote the results of bitter melon chips online so that they can cover a wider market. The output of the program is to be able to empower the MSME community to further improve their business and also be able to improve the quality and quantity of bitter gourd chips by using vacuum frying, providing understanding to bitter melon chip craftsmen with the application of marketplaces in optimizing product marketing.